Articulating Factors Defining RMS Delay Spread in LV PLC Networks - Güzelgöz, Sabih; Çelebi, Hasan Basri; Arslan, Hüseyin (Journal of Computer Systems, Networks, and Communications, 2010)
Communication over the power line network (PLN) referred as power line communication (PLC) has a long history ofnarrowband applications. With the recent developments in the field of digital communications, current interest is to exploitthis medium for wideband communications for several applications such as Internet access, home networking, and in-vehicle datacommunication. In line with this recently emerging interest which envisions the conversion of a power transmissionnetwork into a communication network, understanding the root-mean-squared (RMS) delay spread is essential for multipath PLCchannels for the establishment of reliable communication systems. In this paper, factors that play a role on the RMS delay spreadvalue of low voltage (LV) PLC channels are articulated. Among these factors, dependency of the RMS delay spread on attenuation,loading, and physical characteristics of the communication channel in the PLNs is investigated.